Utilization of Documentary Videos from Historical Heritage Studies (KPS) As a Media for Learning History - Yuniati, Yuniati (Indonesian Journal of History Education, 2018)
The purpose of this study is multifaceted, aiming to (1) determine whether the video documentary PPP results can be effectively utilized as a medium for learning history; (2) assess how students from the History Education Study Program, particularly those from the class of 2011, have been using the documentary video results of KPS as a learning tool; and (3) identify the efforts being made to enhance the KPS course within the department. Analyzing the data and discussions, it is evident that the PPP documentary video can serve as a valuable learning medium. This can be applied in various phases of teaching history, whether as an introduction, a core element, or enrichment material. Furthermore, students from the 2011 cohort of the History Education Department have effectively utilized the KPS documentary video during their classroom activities while conducting Field Practice Experience in History in 2014. The department has consistently strived to develop and refine the PPP course, aiming to improve its quality and effectiveness. These efforts ensure the course meets its objectives and produces the desired educational outcomes.